Berkas Mlaku Dhewe (BMW) untuk Peningkatan Pelayanan Publik di Kabupaten Sidoarjo - Firdha Fitriyani; Arsiyah Arsiyah; Ahmad Riyadh UB (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2017)
This study aimed to describe effectiveness of Berkas Mlaku Dhewe (BMW) as well as analyzed factors supporters and obstacle Berkas Mlaku Dhewe (BMW) in Sukodono District Sidoarjo Regency. The research used descriptive qualitative. The result of research showed that supporters factors that influence the effectiveness of service intranet Berkas Mlaku Dhewe (BMW) in Sukodono who viewed from criterion effectiveness, among others: product was already good because the service administration of population more easy and quickly with system online; efficiency of the speed service was either because the service quite processed in village and file finished with a matter of hours; satisfaction was good because it had supported by the attitude of the manners employees; adaptation had been reviewed from the number of employees and means inadequate infrastructure already according to standards; the development was success that was seen from the innovation of the service online up to the village. In addition, from size of the criterion effectiveness also cause obstacle factor that influence the service intranet in Sukodono Subdistrict include: efficiency reviewed from the settlement kind of the service residence indentification card (KTP) because delay blanko from centre; adaptation of human resources was less spirit in learning information technology because factors elderly; development reviewed from the structure of working menchanism in system of tissue who experience problems network.